Examination the Corrosion Inhibition of Synthesized Azo-Schiff Bases Compounds from (P-Fluorophenyl)-1,3,4-Thiadiazoles for Carbon Steel Alloy in Acidic Medium - Zaidane , Khadija; Naser, Ahmed (Al-Khwarizmi Engineering Journal, 2025)
New azo-Schiff base compounds were prepared by different processes using (p-fluorophenyl)-1,3,4-thiadiazoles, and their role as corrosion inhibitors for carbon steel alloy in acidic media such as 0.1 M HCl at 298 K was investigated. Spectroscopic methods such as FT-IR and NMR were used to characterise the compounds, and potentiodynamic polarization curves were employed to evaluate their corrosion inhibition. p-Aminoacetophenone was react withed 2-(5-(4-fluorophenyl)-1,3,4-thiadiazol-2-yl) acetohydrazide (A1) to prepare N ′-(1-(4-aminophenyl) ethylidene)-2-(5-(4-fluorophenyl)-1,3,4-thiadiazol-2-yl) acetohydrazide (A2). Azo-Schiff bases (A3-A6) were synthesised by combining the prepared diazonium salts with different phenols. These compounds’ structures were changed to improve their ability to prevent corrosion in a range of industrial settings, especially for metals exposed to acidic environments. The inhibitory efficiency percentage was between 76% and 90%. At 90%, the synthetic medication (A6) obtained the highest value. The formed protective adsorption coating on the steel surface was the reason for the improved inhibitor activity. These findings imply that the artificial Azo-Schiff bases show promising application as corrosion inhibitors for carbon steel in acidic settings. Applications in sectors where corrosion resistance is crucial may benefit from this knowledge.